Hospital Payer and Racial/Ethnic Mix at Private Academic Medical Centers in Boston and New York City. (July 2017) - Tikkanen, Roosa Sofia; Woolhandler, Steffie; Himmelstein, David U.; Kressin, Nancy R.; Hanchate, Amresh; Lin, Meng-Yun; McCormick, Danny; Lasser, Karen E.
Academic medical centers (AMCs) are widely perceived as providing the highest-quality medical care. To investigate disparities in access to such care, we studied the racial/ethnic and payer mixes at private AMCs of New York City (NYC) and Boston, two cities where these prestigious institutions play a dominant role in the health care system. We used individual-level inpatient discharge data for acute care hospitals to examine the degree of hospital racial/ethnic and insurance segregation in both cities using the Index of Dissimilarity, together with recent changes in patterns of care in NYC. In multivariable logistic regression analyses, black patients in NYC were two to three times less likely than whites, and uninsured patients approximately five times less likely than privately insured patients, to be discharged from AMCs. In Boston, minorities were overrepresented at AMCs relative to other hospitals. NYC hospitals were more segregated overall according to race/ethnicity and insurance than Boston hospitals, and insurance segregation became more pronounced in NYC after the Affordable Care Act. Although health reform improved access to insurance, access to AMCs remains limited for disadvantaged populations, which may undermine the quality of care available to these groups.